Management of dyslipidaemia in patients with coronary heart disease: Results from the ESC-EORP EUROASPIRE V survey in 27 countries - Jankowski, Piotr; Reiner, Željko; De Backer, G.; Abreu, A.; Bruthans, J.; Cifkova, R.; Dilic, M.; Dolzhenko, M.; Lovic, D.; Reiner, Ž.; Rydén, L.; Tsioufis, K.; et al. (Atherosclerosis, 2019)
One of the objectives of the ESC-EORP EUROASPIRE V survey is to determine how well European guidelines on the management of dyslipidaemias are implemented in coronary patients. Standardized methods were used by trained technicians to collect information on 7824 patients from 130 centers in 27 countries, from the medical records and at a visit at least 6 months after hospitalization for a coronary event. All lipid measurements were performed in one central laboratory. Patients were divided into three groups: on high-intensity LDL-C-lowering-drug therapy (LLT), on low or moderate-intensity LLT and on no LLT. At the time of the visit, almost half of the patients were on a high-intensity LLT. Between hospital discharge and the visit, LLT had been reduced in intensity or interrupted in 20.8% of the patients and had been started or increased in intensity in 11.7%. In those who had interrupted LLT or had reduced the intensity, intolerance to LLT and the advice of their physician were reported as the reason why in 15.8 and 36.8% of the cases, respectively. LDL-C control was better in those on a high-intensity LLT compared to those on low or moderate intensity LLT. LDL-C control was better in men than women and in patients with self-reported diabetes. The results of the EUROASPIRE V survey show that most coronary patients have a less than optimal management of LDL-C. More professional strategies are needed, aiming at lifestyle changes and LLT adapted to the need of the individual patient. [Display omitted] •Most patients with established coronary artery disease have suboptimal lipid management.•More professional strategies are needed aiming at lifestyle changes and LLT adapted to the need of the individual patient.•The striking variability between countries and centers with several examples of well managed patients illustrates that the present conditions can be improved.